Comparative study on the lipidlowering and antioxidant effects of acupuncture in Gansoo(BL18).Pungji(GB20) and Eumnungcheun(SP9) of hyperlipidemic rat -centering around biochemical and molecular biological discuss - Lee Joon-Moo; Lim Kwan-II (Korean Pharmacopuncture Institute, 2002)
The lipid lowering and antioxidant effects of Gansoo(BL18), Pungji(GB20) and Eumnungcheun(SP9) acupuncture in rats fed high fat diet were analyzed in biochemical and molecular biological aspects. The results obtained from this study are as follows : 1. In the body weight reduction, all acupuncture groups showed a high reduction compared to those of control group and in acupuncture groups, Gansoo(BL18) and Pungji(GB20) acupuncture groups showed a high reduction. 2. The concentration of plasma triglyceride, total cholesterol and LDL-cholesterol with acupuncture groups showed a little decrease and in acupuncture groups, Gansoo(BL18) and Pungji(GB20) groups showed a low values compared to those of other acupuncture groups. However, the tendency of HDL-cholesterol concentration showed no significant different. 3. The concentration of plasma b-lipoprotein and free fatty acids showed a lowest values in the Gansoo(BL18) and Pungji(GB20) acupuncture groups and the glucose concentration showed to decrease in all treated acupuncture groups. 4. The concentration of liver total cholesterol and triglyceride in Gansoo(BL18) and Pungji(GB20) acupuncture groups showed a lower values than those of control group. 5. In all the acupuncture groups, the plasma glutamic oxaloacetic transaminase(GOT) activity showed a little decrease. In the glutamic pyruvate activity(GPT), Gansoo(BL18) and Pungji(GB20) acupuncture groups showed a lower values than those of control groups. However the values of eumneungcheun acupuncture only group showed no significant difference to those of control group. 6. The plasma and liver Thiobabituric acid reactive substance (TBARS) concentration in Gansoo(BL18) and Pungji(GB20) acupuncture groups were a lower than those of control group. However the values of eumneungcheun acupuncture group showed no significant difference to control group. 7. The superoxide dismutase (SOD) activity in Gansoo(BL18) acupuncture group and Glutathione peroxidase (GSH-Px) activity in Gansoo(BL18) and Pungji(GB20) acupuncture groups showed a high values. The catalase (CAT) activity in all the acupuncture groups showed a higher values than those of control group. 8. In acupuncture groups, DNA expression of Apo-B and Apo-E showed a tendency to decrease, however DNA expression of leptin showed no significant difference in all treatment groups. DNA expression of TNF-a showed a increase in acupuncture groups. These results indicate that Gansoo(BL18) and Pungji(GB20) (especially Gansoo(BL18)) acupuncture affect the lipid metabolism and showed possibility of lowering adipose tissue mass and lipid peroxidation.